Obstacles to the Implementation of the Islamic Education Curriculum: Analysis of Problems and Strategic Solutions - Junaidi; Tatik Ambariyah; Nurul Mubin (LP3M KH Yazid Karimullah Institute, 2026)
This study aims to analyze the obstacles in the implementation of the Islamic Religious Education (PAI) curriculum and formulate strategic solutions to improve learning effectiveness. The study used a qualitative approach with a case study conducted in educational units. Data collection techniques included observation, in-depth interviews, and documentation, with data analysis techniques through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the PAI curriculum has not been optimal, which is characterized by the dominance of teacher-centered learning methods, limited pedagogical and professional competencies of teachers, and gaps between learning planning and implementation. In addition, external factors such as the family environment, society, and the development of information technology also influence the effectiveness of PAI learning. The impact of these various obstacles is seen in the less than optimal achievement of learning objectives, particularly in the affective and psychomotor aspects of students. Therefore, strategic solutions are needed in the form of improving teacher competency through continuous training, optimizing facilities and infrastructure, developing a comprehensive evaluation system, and strengthening collaboration between schools, families, and the community. This research is expected to contribute to the development of a more effective, contextual, and adaptive PAI curriculum implementation to meet the challenges of the times.